Sosialisasi Nursery Rhymes sebagai Media Pembelajaran Bahasa Inggris Bagi Guru TK di Kecamatan Kotabumi Kota - Novia, Sinta; Setiani , Rulik; Munisah , Eny (INCOME: Indonesian Journal of Community Service and Engagement, 2025)
Curiosity and desire to learn in early childhood seem low, especially in terms of introducing English because it is considered difficult and boring. To overcome this problem, educators and teachers must try to teach English in a fun way. Nursery Rhymes, children's songs, or simple poems in English are ideal educational resources for early childhood. However, most kindergarten teachers in Kotabumi Kota District still face various challenges when using technology and making creative learning innovations. The PkM activity aims to socialize the effective and fun Nursery Rhymes English learning media for kindergarten children to kindergarten teachers in Kotabumi Kota District. This activity was carried out at ABA 1 Kindergarten Kotabumi and was attended by ABA Kindergarten teachers throughout Kotabumi Kota District and all ABA Kindergarten teachers from the North Lampung region. This PkM activity was carried out well and successfully. The results of this PkM activity showed an increase and understanding of teachers about fun and interactive methods that can be applied to early childhood children in introducing English.